Experts’ perception of artificial intelligence knowledge in Egyptian newsrooms - Sarah Elaasser; Mervat Abo Oaf; Sally Tayie (Insights into Language, Culture and Communication)
As artificial intelligence technologies are emerging and changing various fields including journalism, it is important to understand the extent of AI knowledge that newsrooms have. This study explores the perceptions of experts regarding artificial intelligence (AI) knowledge in Egyptian newsrooms. This paper employs the AI readiness and AI adoption model which includes the phases of AI adoption, and five variables that affect the adoption process. Through in-depth interviews, the research focuses on the AI knowledge variable which includes several aspects: AI awareness, upskilling efforts, and ethical concerns among journalists and managers in organizations integrating AI.  The study reveals a lack of comprehensive understanding of AI within news organizations. Upskilling initiatives vary among organizations. Experts call for regulations and ethical guidelines to face ethical concerns including accuracy, copyrights, bias, and privacy invasion. The study emphasizes the urgency of addressing AI literacy and training while managing the ethical implications of AI in journalism.   Received: 08 November 2023 Accepted: 14 January 2024 Published: 17 April 2024